Shifting the information organization module implementation of library management system from client-server architecture to web-based application / Wan Ainol Mursyida Ahmad Tarmizi, Saidatul Akmar Ismail and Ahmad Zam Hariro Samsudin - Ahmad Tarmizi, Wan Ainol Mursyida; Ismail, Saidatul Akmar; Samsudin, Ahmad Zam Hariro (Faculty of Information Management, 2022)
This paper is about the development of Web based Cataloging System as a solution to replace the client-based cataloging system. The sole prerequisite for using this cataloguing system is internet connectivity. In comparison to clientbased cataloguing systems, web-based cataloguing systems offer shorter and more convenient installation times. In order to address issues users of clientbased cataloguing systems have, the main goal of this project is to investigate web-based cataloguing systems. Creating a web-based cataloguing system will help users with issues they have with client-based cataloguing systems. to assess the system for online cataloguing. The library system and its corresponding webbased user interface are the main subjects of the study. The library system, which is a comprehensive system in the education sector, comprises of more than 20 modules. One of the major modules, the cataloguing module, will be the main topic of development and research for this project. In order to catalogue library materials, a librarian must complete a number of tasks in this module. These functions-save, save and index, index, unindexed, duplicate record, delete record, search from index and buffer, add tag, term search, add subfield, non-filling indicator, and authority link-will be built for this cataloguing module. With the help of the function save, librarians can catalogue library resources and temporarily save them in a table.